STRATEGI INDONESIA MENGATASI TUMPANG TINDIH ZEE INDONESIA-VIETNAM DI PERAIRAN NATUNA UTARA TAHUN 2017-2019 - Junita, Ratna; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study discusses the problem of overlapping claims of the  Exclusive Economic Zone (EZZ) between Indonesia and Vietnam in North Natuna Waters in 2017-2019. Indonesia’s vast sea area allows for border disputes with neighboring counries, especially if the country’s maritime boundaries have not been resolved. In addition to causing disputes, it also raises other problems such as illegal fishing violations in the jurisdiction and ownership of indonesia. In discussing the various overlapping EZZs, the authors use qualitative research methods, with data collection techniques based on library research derived form literary sources such as books, journals, official documents, and scientific articles. The perspective that the author uses is the Realism Perspective, which always prioritizes the interests of the state in making any policy. This study uses Border Dispute Theory which relates values and other problems that expand the boundary problem.This study shows that in an insignificant negotiation between the two countries, the difference in views between the EZZ regime and the Continental Shelf, causing the results of the negotiations between Indonesia and Vietnam to be not very favorable for Indonesia. The problem of overlapping EZZ boundaries causes other problems such as the number of illegal fishing carried out by neighboring countries, especially by Vietnam. Thus, Indonesia took firm action by implementing the Sink The Vessel (STV) Policy to reduce the occurrence of fishing violations in Indonesian jurisdictions. Now negotiations on national borders to resolve border are still being carried out by the second country to strengthen border diplomacy.Key Notes: EEZ, Border Dispute, Illegal Fishing, STV, Vietnam.